Étude des différences intersexes sur le plan des conflits entre le travail et les rôles familiaux auprès de professionnels - Lachance, Lise; Brassard, Nathalie; Tétreau, Bernard (Canadian Journal of Counselling and Psychotherapy, 2007)
Comparative studies between men and women on work-family conflict have shown contradictory results. These results may be explained by a lack of control over confounding variables (age, income, education, etc.). This study compares professional men and women, matched by age and job title, on work-family conflict and other associated variables. Results suggest there are more similarities than differences between genders, although some of the differences that were observed actually reinforce traditional role models. Men and women’s careers may therefore differ because of the socialization process.